Benefit of linking hospital resource information and patient-level stroke registry data. (24th January 2023) - Purvis, Tara; Cadilhac, Dominique A; Hill, Kelvin; Gibbs, Adele K; Ghuliani, Jot; Middleton, Sandy; Kilkenny, Monique F
Abstract: Variation in the delivery of evidence-based care affects outcomes for patients with stroke. A range of hospital (organizational), patient, and clinical factors can affect care delivery. Clinical registries are widely used to monitor stroke care and guide quality improvement efforts within hospitals. However, hospital features are rarely collected. We aimed to explore the influence of hospital resources for stroke, in metropolitan and regional/rural hospitals, on the provision of evidence-based patient care and outcomes. The 2017 National Audit organizational survey (Australia) was linked to patient-level data from the Australian Stroke Clinical Registry (2016–2017 admissions). Regression models were used to assess the associations between hospital resources (based on the 2015 Australian National Acute Stroke Services Framework) and patient care (reflective of national guideline recommendations), as well as 90–180-day readmissions and health-related quality of life. Models were adjusted for patient factors, including the severity of stroke. Fifty-two out of 127 hospitals with organizational survey data were merged with 22 832 Australian Stroke Clinical Registry patients with an admission for a first-ever stroke or transient ischaemic attack (median age 75 years, 55% male, and 66% ischaemic). In metropolitan hospitals ( n = 42, 20 977 patients, 1701 thrombolyzed, and 2395 readmitted between 90 and 180 days post stroke), a faster median door-to-needle time for thrombolysis was associated with ≥500 annual stroke admissions [−15.9 minutes, 95% confidence interval (CI) −27.2, −4.7], annual thrombolysis >20 patients (−20.2 minutes, 95% CI −32.0, −8.3), and having specialist stroke staff (dedicated medical lead and stroke coordinator; −12.7 minutes, 95% CI −25.0, −0.4). A reduced likelihood of all-cause readmissions between 90 and 180 days was evident in metropolitan hospitals using care pathways for stroke management (odds ratio 0.82, 95% CI 0.67–0.99). In regional/rural hospitals ( n = 10, 1855 patients), being discharged with a care plan was also associated with the use of stroke clinical pathways (odds ratio 3.58, 95% CI 1.45–8.82). No specific hospital resources influenced 90–180-day health-related quality of life. Relevant to all international registries, integrating information about hospital resources with clinical registry data provides greater insights into factors that influence evidence-based care.